MACROFAUNA EM DIFERENTES SISTEMAS DE USO DO SOLO NA AGRICULTURA FAMILIAR NO MUNICÍPIO DE TACURU, MATO GROSSO DO SUL - LOPES, Emily Kamila de Souza; AGUIAR, Allan Kardec Moreira; ROSSET, Jean Sérgio; CASTILHO, Selene Cristina de Pierri; MARRA, Leandro Marciano (ANAIS DO ENIC, 2020)
-